EVALUATION OF THE DEPARTMENT OF DEFENSE INSTALLATION MOSQUITO SURVEILLANCE PROGRAM, UNITED STATES 2012-2015 - Dawes, Terra L. (My University, 2016)
West Nile virus (WNV) is the primary arbovirus acquired within the United States and is transmitted by the bite of a mosquito. Mosquito surveillance programs are key components of overall WNV disease surveillance programs at the local, state, and federal levels. The valuable information collected from mosquito surveillance is used to direct methods to protect public health. To consolidate human and nonhuman (including mosquito surveillance) WNV surveillance data from all states, the Centers for Disease Control and Prevention (CDC) partnered with state public health departments and created ArboNET, the national arboviral surveillance system. Mosquito surveillance programs on Department of Defense (DoD) installations provide valuable information on WNV surveillance within their state. This study was the first to evaluate ArboNET WNV mosquito surveillance data to determine if DoD installations reported to state health departments. Mosquito surveillance data was received from the Army Public Health Center (Provisional) and the Air Force School of Aerospace Medicine. Data was reviewed from 2012-2015 for Army and Air Force installations and cross- referenced with an ArboNET dataset from the CDC. From 2012-2015, Army installations did not report 46.6% (range of 0-86% annually) and Air Force installations did not report 47.4% (range of 16-81% annually) of WNV positive mosquito pools to state public health departments for inclusion into ArboNET. Improved communication, standardization of data fields collected during surveillance, and a standardized database to collect mosquito surveillance data from DoD installations could aid in the improvement of mosquito surveillance data to state health departments.
Keywords: West Nile Virus; Mosquito Surveillance; ArboNET